Fast Lasing Wavelength Tuning in Single Nanowires. Issue 20 (5th August 2019) - Xu, Peizhen; Gong, Jue; Guo, Xin; Xin, Chenguang; Wu, Hao; Qing, Peng; Lin, Xing; Fang, Wei; Di, Dawei; Tong, Limin
Abstract: Nanowire lasers hold great potential as nanoscale coherent light sources. The rapid wavelength tuning of such light sources is one of the most important parameters for practical applications. Although significant efforts have been made in the past decades, the fast and reversible lasing wavelength tuning in nanowires or structures alike remains a challenge. Here, by incorporating temperature‐dependent Varshni shift of the bandgap with ultralow thermal inertia of a free‐standing cadmium sulfide (CdS) nanowire, a fast lasing wavelength tuning in single nanowires with excellent reversibility is demonstrated. Above room temperature, a Varshni shift rate (≈0.16 nm K −1 ) twice larger than that at low temperature (≈ 0.085 nm K −1 ) is observed, and the nanowire lasing peak is tuned from 514 to 549 nm with step down to 0.075 nm K −1 . Using a beam of CO2 laser pulses to instantaneously modulate the temperature of a free‐standing lasing nanowire, a reversible wavelength tuning at a rate of ≈48 000 nm s −1, which is about three orders of magnitude faster than that reported previously is achieved. The results herein suggest a very promising route to fast wavelength tuning in lasing nanowires or other nanostructures, which may lead to fast tunable nanolasers for a variety of nanophotonic applications. Abstract : A novel approach to fast lasing wavelength tuning in single CdS nanowires with excellent reversibility is introduced. Using a beam of CO2 laser pulses to instantaneously modulate the temperature of a free‐standing lasing nanowire, a reversible wavelength tuning at a rate of ≈48 000 nm s −1 is achieved via Varshni shift of the bandgap. These results pave the way toward high‐speed thermo‐optical devices on nanometer scale.